Therapeutic communication in survivors of obsessive-compulsive disorder: A Twitter analysis - Siregar, Nina Siti Salmaniah; Lu, Jiaqing; Waridah, Waridah; Tamsil, Ilma Saakinah (Jurnal Studi Komunikasi, 2022)
Mental or psychiatric disorders are problems experienced by some people. There are several types of mental disorders, such as anxiety, mood, or eating disorders. This problem affects how sufferers think and behave, like obsessive-compulsive disorder (OCD). A mental disorder makes sufferers have thoughts and behaviours that are not controlled (obsessions) to do something repeatedly (compulsively). The action can also interfere with the sufferers' daily activities and social interactions. This study aimed to determine therapeutic communication in survivors of obsessive-compulsive disorder (OCD). The method used in this research is phenomenology, where the informants in this study are survivors of obsessive-compulsive disorder (OCD). The conclusion of this study shows that therapists engage in therapeutic communication with Obsessive-Compulsive Disorder (OCD) survivors using a form of psychological therapy that helps OCD survivors overcome their worries and obsessive thoughts without coercion. This is done by raising the ability to pay attention, empathy, and the ability to respond.